2005
DOI: 10.1101/lm.88005
|View full text |Cite
|
Sign up to set email alerts
|

Insulin receptor signaling in long-term memory consolidation following spatial learning

Abstract: Evidence has shown that the insulin and insulin receptor (IR) play a role in cognitive function. However, the detailed mechanisms underlying insulin's action on learning and memory are not yet understood. Here we investigated changes in long-term memory-associated expression of the IR and downstream molecules in the rat hippocampus. After long-term memory consolidation following a water maze learning experience, gene expression of IR showed an up-regulation in the CA1, but a down-regulation in the CA3 region. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
144
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(148 citation statements)
references
References 49 publications
1
144
0
3
Order By: Relevance
“…Here, we describe a pathogenic mechanism by which a type of "brain diabetes" is triggered by AβOs, synaptotoxins that accumulate in AD brains. Because brain insulin signaling is centrally involved in learning and memory (8), the impact of AβOs on brain insulin signaling may be a mechanism potentially contributing to early memory loss in AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we describe a pathogenic mechanism by which a type of "brain diabetes" is triggered by AβOs, synaptotoxins that accumulate in AD brains. Because brain insulin signaling is centrally involved in learning and memory (8), the impact of AβOs on brain insulin signaling may be a mechanism potentially contributing to early memory loss in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Brain levels of insulin and insulin receptor (IR) are lower in AD, and insulin signaling impairments have been documented in both postmortem analysis and in animal models of AD (3)(4)(5)(6). Brain insulin signaling is particularly important for learning and memory (7,8), suggesting that insulin resistance may contribute to cognitive deficits in AD.…”
Section: Introductionmentioning
confidence: 99%
“…Bruehl et al (35) reported that adolescents with type 2 DM with insulin resistance have significantly reduced hippocampal and prefrontal volumes and higher rates of global cerebral atrophy as compared with obese controls without insulin resistance. Insulin and insulin receptor signaling play a modulatory role in learning and memory processing (36). The role of hyperinsulinemia and abnormalities in insulin signaling within the brain need to be studied because they might explain some of the apparent differential effects of type 1 diabetes and type 2 diabetes on the brain.…”
Section: Discussionmentioning
confidence: 99%
“…The role of insulin in synaptic plasticity and cognitive function is well established in humans and in animal models (e.g. Dou et al, 2005;Chiu et al, 2008;Oda et al, 2011) (reviewed by Chiu and Cline, 2010;Bosco et al, 2011;Kapogiannis and Mattson, 2011). In Drosophila, targeted inhibition of phosphatidylinositol 3-kinase (PI3K) was recently used to reduce synapse number to model the sensory perception decline characteristic of ageing and neurodegenerative diseases (Acebes et al, 2011).…”
Section: Introductionmentioning
confidence: 99%